Citizens’ health practices during the COVID -19 pandemic in Indonesia: Applying the health belief model - Winarti, Eko; Umbul Wahyuni, Chatarina; Andy Rias, Yohanes; Agung Mirasa, Yudied; Sidabutar, Sondang; Lusiana Wardhani, Desi (Belitung Raya Foundation, Indonesia, 2021)
Background: Understanding the health practice of Indonesian residents and its related factors during the COVID-19 pandemic is crucial, but such association necessitates clarity. Objective: To examine the health practices of the Indonesian citizens and their correlations with knowledge and health belief model (perceived susceptibility, barriers, benefits, severity, and self-efficacy) during the COVID-19 pandemic. Methods: A community-based online cross-sectional design was employed. The study was conducted from 10 July to 30 August 2020 among 552 citizens selected using convenience sampling. Sociodemographic characteristics, knowledge, health belief model, and health practices, including wearing a mask, social distancing, and washing hands, were measured using validated questionnaires. Adjusted odds ratios (AORs) and logistic regression were employed for data analysis. Results: The adjusted AORs (95% CIs) of a good level of health practices—wearing the mask, social distancing, and washing hands—were 3.24 (1.52 6.89), 2.54 (1.47 4.39), and 2.11 (1.19 3.75), respectively, in citizens with the high level of knowledge. Interestingly, respondents with positively perceived susceptibility exhibited significantly good practice in wearing the mask (4.91; 2.34 10.31), social distancing (1.95; 1.08 3.52), and washing hands (3.99; 2.26 7.05) compared to those with negatively perceived susceptibility. In addition, perceived barriers, benefits, severity, and self-efficacy also exhibited a significantly good all variables of health practice regarding COVID-19 pandemic after adjusting for confounding variables. Conclusion: Citizens with high levels of knowledge and positive levels of the health belief model had good practice of wearing masks, social distancing, and washing hands. The outcomes of this survey could encourage health professionals, including nurses, through management practices of nursing intervention based on the health belief model during the pandemic.